Pertanggungjawaban Pidana US Terkait Kegiatan Pengelolaan Lahan Di Kawasan Hutan Secara Tidak Sah Ditinjau Dari Undang-Undang Nomor 41 Tahun 1999 Tentang Kehutanan - Haryanto, Cindy Angelin (Jurnal Panorama Hukum, 2020)
Environment is everything that exists around human life whose existence is directly and indirectly very influential on the survival of humans and other living things. The environment is an absolute part of human life. Regarding the environment, it has been regulated in the 1945 Constitution of the Republic of Indonesia Article 28H paragraph (1), which determines that every person has the right to live physically and mentally, live and get a good and healthy environment and the right to obtain health services. A good and healthy environment is a right that must be obtained by all Indonesian citizens because it has been regulated in the 1945 Constitution. Indonesia is one of the countries with the highest biodiversity in the world, all of which are in the Indonesian Tropical Forest. With the size of forests in Indonesia and other natural resources, many people manage or use forest land illegally or without permission. Damage to the environment will give a huge loss to people's lives in Indonesia.